2012
DOI: 10.1111/j.1469-8749.2012.04264.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessing educational outcomes in middle childhood: validation of the Teacher Academic Attainment Scale

Abstract: SEN Special educational needs TAAS Teacher Academic Attainment Scale WIAT-II Wechsler Individual Achievement Test, 2nd (UK) editionAIM Assessing educational outcomes in high-risk populations is crucial for defining long-term outcomes. As standardized tests are costly and time-consuming, we assessed the use of the Teacher Academic Attainment Scale (TAAS) as an outcome measure.METHOD Three hundred and forty three children in mainstream schools aged 10 to 11 years (144 males, 199 females; 190 extremely preterm an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 29 publications
2
10
1
Order By: Relevance
“…The observed between-group discrepancies in performance are consistent with previous studies that have reported significant deficits in academic performance in EP children, with the most substantial differences in standardized measures of attainment in mathematics as compared with other school subjects (3,14,17).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The observed between-group discrepancies in performance are consistent with previous studies that have reported significant deficits in academic performance in EP children, with the most substantial differences in standardized measures of attainment in mathematics as compared with other school subjects (3,14,17).…”
Section: Discussionsupporting
confidence: 89%
“…EP children did not perform as well as control children on either of these scales; EP children had greater difficulty with processing simultaneously presented information rather than sequentially presented information, a result replicating those of previous studies (13,14). In fact, simultaneous, rather than sequential, processing score was a stronger predictor of WIAT-MS for the EP group; the reverse was true for control children.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Ratings were on a five point likert scale and ranged from one (very below average) to five (very above average). The TAAS has excellent validity when compared with results on gold standard achievement tests [34]. Teachers were also asked to specify whether the child had SEN, defined in the UK as a learning difficulty or disability which calls for special educational provision to be made, or the child has a disability which prevents or hinders him or her from making use of educational facilities of a kind generally provided for other children of the same age in mainstream schools [35].…”
Section: Teacher Reportmentioning
confidence: 99%